Profile of exudative pleural effusion in the region of Bhuj people - Desai, Vishal K.; Arora, Rashmi S. (International Journal of Advances in Medicine, 2018)
Background: Exudative pleural effusions are a common diagnostic problem in clinical practice, as the list of causes is quite exhaustive, although sometimes they can be inferred from the clinical picture. In the West the most common cause is Para pneumonic effusions followed by malignancy, while in India it is tubercular effusion followed by malignant effusion. Despite the availability of various tests, there is a need for deﬁning the best diagnostic and cost-effective approach to quickly diagnose and treat exudative pleural effusions. The objectives are to conduct a clinical and etiological study of exudative pleural effusion, to evaluate biochemical proﬁle, cytological proﬁle and radiological proﬁles of exudative pleural effusion. Methods: Prospective study of 100 patients with exudative pleural effusions. The demographic data was expressed as mean±standard deviation. Comparison between groups was done by Chi-Square test and Fischer exact test for categorical variables and Kruskar-Wallis and Mann-Whitney tests for continuous variables. Results: There were 67 males and 33 females. The mean age was 41.6±15.74. The majority were tubercular in origin (67%),13%,8%,3%and 6% were malignant effusions, Synpneumonic effusion, pancreatic effusions and empyema respectively. Diagnosis was not established in 3% of effusions. Massive effusions were seen in 53.8% of malignant effusions and 33.3% of empyemas. Most effusions had a total cell count between 1000 to 5000 cells /mm3.Lymphocyte predominant effusions were seen in 84.6% and 89.6% of malignant and tubercular effusions. 61.5% of malignant effusions had a positive cytology. Tubercular effusion had a pleural ﬂuid ADA more than 40 IU/L. 92.3% of malignant effusion had pleural ﬂuid ADA less than 30IU. Conclusions: Pleural effusion is a commonly encountered in medical practice and in our country, the commonest cause is tuberculosis, as is evidenced from the present study. The initial step in evaluating case of pleural effusion is to establish the cause of pleural effusion which is done by a detailed history, clinical examination and investigations like a chest radiology and pleural ﬂuid analysis. Even in the advanced diagnostic approaches, still detailed clinical history and examination of the patient of the patient is important to make a clinical diagnosis. All suspected cases of pleural effusion should undergo Sonography of the thorax along with routine chest x-ray. Fluid cytology should be done to conﬁrm tuberculosis or to rule out malignancy, which guides the physician for further evaluation of the patient if required.